Engineering and reclamation of the Holden Legacy Mine — advancing the state-of-practice for mine closure - Cline, DJ; Crouse, PE; DeDen, FM; Zimmer, TR (Mine Closure 2016: 11th International Conference on Mine Closure, 2016)
Rio Tinto is reclaiming an abandoned copper mine in one of the most isolated places in the continental U.S., located near Lake Chelan in the remote reaches of north-central Washington State. The Holden Mine was one of the largest operating underground copper mines in the U.S.; the mine was developed and operated between 1937 and 1957 and produced over 90,000 tonnes of copper, as well as zinc, silver and gold. Over the life of the mine, nearly 100 km of underground tunnels had been excavated and 7.6 million tonnes of mill tailings placed on U.S. National Forest lands near Railroad Creek. Although Rio Tinto never owned or operated the mine, they are managing and funding a several hundred million dollar clean-up to prevent future water and soil contamination and to restore the former mine site under the United States Environmental Protection Agency Superfund process. Adjacent to the mine is a former man camp, now home of the Holden Village Inc., a religious community that hosts 5,000 to 6,000 visitors each year. Engineering the Holden Mine remedial design required development of an integrated system of mine closure components including: infrastructure improvements, surface water and sediment management, slope stability improvements, surface and groundwater collection and treatment, mill demolition, and restoration to re-establish vegetation consistent with that of the surrounding forest. This paper addresses these topics and includes information on the design criteria and objectives, pre-design investigations and evaluations, and a summary of the design for each remedial component. The paper concludes with the project successes and lessons learned from engineering the remedial design. The first in a series of technical papers, this paper provides the mine closure community an overview of the innovative design and construction techniques that have been applied at the Holden Mine with the goal of further advancing the state-of-practice for mine closure and remediation at other sites.
Keywords: legacy; reclamation; remediation; design; case study